Tumor-targeted upconverting nanoplatform constructed by host-guest interaction for near-infrared-light-actuated synergistic photodynamic-/chemotherapy - Yao, Xuemei (2022)
The strategic combination of photodynamic therapy and chemotherapy has emerged as a promising treatment option for various tumor indications, which not only expands our understanding of each individual modality but also reveals new opportunities to achieve superadditive benefit via exploring their internal synergy rather than simple mixing. In this study, dual-emissive upconverting nanoparticle (UCNP) was employed to bridge the two treatment regimens to synergistically reinforce the therapeutic efficacy. The UCNP-based drug delivery nanoplatform was first co-loaded with 1,8-dihydroxy-3-methylanthraquinone (DHMA) photosensitizers and UV-activatable camptothecin prodrug (NBCCPT) and then complexed with biofunctional β-cyclodextrin species (β-CD-PEG-LA) via highly specific host-guest interactions to cap the camptothecin prodrug conjugated on the nanoparticle surface. The supramolecularly attached β-CD-PEG-LA could not only enhance the aqueous dispersity of the nanocarriers and prevent DHMA leakage, but also imbues targeting effect against asialoglycoprotein receptor-overexpressing tumor cells. The UCNP core would convert the NIR excitation (980 nm) into localized UV (360 nm) and visible (480 nm) emissions, of which the former would cleave the nitrobenzene linker to restore the cytotoxicity of CPT while the latter could excite the photosensitizer to generate reactive oxygen species (ROS). In addition to the photodynamic damage, the light-generated ROS could also facilitate the endo/lysosomal escape of the endocytosed nanoparticles and improve the overall antitumor potency in a synergistic manner.